The Main Roles of Economic Ethics in the Preparation of Future conomists - Pechočiaková Svitačová, Eva (Civilia, 2021)
The quality life of people in companies is considerably dependent on the economy and in relation to the preparation of a young generation for the implementation of the economy's activities is the attention focus on economic ethics, which is one of the types of applied ethics. The contribution points to the need for its implementation in the education of future economy experts, even with regard to the change in dominating paradigm in education "education for profit". It justifies that, in order to ensure the quality life of people in companies, decent access to them and ensuring human and socio-economic development helps economic ethics, but also some other applied ethics for the economy and economy, prepare a young generation for the humanize of the economy. Implementation of economic ethics to an educational process is to allow future experts in the economy to understand the real reasons for the renaissance of the basic objective of the economy, and also to ensure human resources approaches, and finally to reform the entire economy in favor of a person.
Keywords: Education; Economy; Economic ethics; Humanization of economy; Future experts in economy